2010
DOI: 10.1177/0734282910380191
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity Evidence of the Chinese Piers-Harris Children’s Self-Concept Scale Scores Among Taiwanese Children

Abstract: The Piers-Harris Children's Self-Concept Scale-Second Edition (Piers-Harris 2) was designed to measure self-concept among children and adolescents. This study aimed to assess the reliability and validity of the scores of the Chinese version of the Piers-Harris 2 (Chinese Piers-Harris). The Chinese Piers-Harris 2 was administered to 243 Taiwanese students in Grades 1 to 4. The results of factor analysis indicated a six-factor promax solution was the most appropriate solution for the Chinese Piers-Harris 2. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
3
0
4
Order By: Relevance
“…The results of assessing the equality of convergence and criterion-related validities suggested that the correlations were equivalent between the multimedia and paper-and-pencil versions of the Piers-Harris 2 scores. The overall results indicate acceptable psychometric qualities of the Chinese multimedia Piers-Harris 2 scores and provided further evidence of the applicability of the translated Piers-Harris 2 to Taiwanese children, consistent with previous studies mentioned earlier [ 27 28 , 31 – 32 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of assessing the equality of convergence and criterion-related validities suggested that the correlations were equivalent between the multimedia and paper-and-pencil versions of the Piers-Harris 2 scores. The overall results indicate acceptable psychometric qualities of the Chinese multimedia Piers-Harris 2 scores and provided further evidence of the applicability of the translated Piers-Harris 2 to Taiwanese children, consistent with previous studies mentioned earlier [ 27 28 , 31 – 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…It could be applicable to children as young as 7 [ 1 , 30 ], and its design seems to match younger children’s cognitive and developmental abilities. The psychometric properties of the translated Chinese paper-and-pencil Piers-Harris 2 were examined, and the results suggested its applicability to Chinese children from age 6 to 15 [ 31 – 32 ]. Considering the developmental needs of younger children, they may benefit from the development of computer-assisted animated self-concept measures with audio or graphic features which could potentially enhance their understanding of abstract concepts such as verbal or written descriptions of self-concept.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument is a widely used scale in assessing popularity among children and adolescents (e.g., Parker, 2010). Flahive, Chuang, and Li (2011) conducted multiple tests with this instrument and concluded that it was stable over time with an internal consistency of more than 0.90. Social anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…A composite score ranging from 0 to 60 is utilized within the current analyses, with higher scores indicating better wellbeing. The reliability and validity of this measure have been demonstrated across a range of samples (Alexopoulos & Foudoulaki, 2002;Flahive, Chuang, & Li, 2011) with internal consistency (alpha) estimates ranging from 0.74 to 0.81 for the subscales and 0.91 for the overall score (Piers et al, 2002).…”
Section: Piers-harris II Children's Self-concept Scalementioning
confidence: 99%